SYMPTOMS VARIATION OF VIRAL INFECTIONS IN YARDLONG BEAN - ., Supyani; Nurul Septariani, Dwiwiyati; ., Hadiwiyono (JURNAL HAMA DAN PENYAKIT TUMBUHAN TROPIKA, 2020)
Yardlong bean (Vigna unguiculata subsp. sesquipedalis L.) is an important horticultural commodity in Indonesia. During the last ten years, yardlong bean planting areas in Indonesia especially in Java often suffered from epidemics of viral disease showing typical symptoms of yellow mosaic on their leaves. Some researchers have separately reported that the symptoms associated with some viral infections. This research aimed to examine viruses associated with the symptoms of yellow mosaic on yardlong bean in endemic areas in Sukoharjo, Central Java, Indonesia. Yardlong bean leaves were taken from the district by purposive sampling method, then the virus was detected by nucleic acid amplification using specific primers for Begomovirus, Bean common mosaic virus (BCMV) and Cucumber mosaic virus (CMV). The results showed that one sample of yardlong bean could be infected by more than one virus. Infection of two kind of virus in a yardlong bean showed symptoms of each virus plus a synergistic effect where the symptoms become more severe.